The Berenstain bears$1 (Btrouble with money s - Berenstain, Stan, 1923-; Berenstain, Jan, 1923- (New York : Random House, 1983)
Brother and Sister Bear learn some important lessons about earning and spending money.
Keywords: Money -- Fiction; Finance, Personal -- Fiction; Moneymaking projects -- Fiction; Bears -- Fiction